PENERAPAN ESG DALAM BISNIS: TINJAUAN BIBLIOMETRIK DAN PERSPEKTIF UTILITARIANISME - Hutabarat, Devi Natalia; Naimah , Zahroh (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2025)
Environmental, social and governance (ESG) aspects have been considered by companies since the emergence of the sustainability development system by the United Nations which is adopted by countries. Companies are trying to implement these three aspects with the aim of mutual welfare of both the company and stakeholders. The intended common interest is one of the goals of the utilitarianism ethical principle. This research aims to analyze the application of ESG based on the utilitarianism principle. This research is a descriptive qualitative and uses bibliometric research methods on scientific articles. The result of this research analysis is that the implementation of ESG will indeed require sacrifices such as company finances but the results will bring welfare to stakeholders, the company's good name and even increase company profits.